Factors Influencing Consumers Purchase Intention Mediated by Immersive Experience: A research agenda - Putri, Anida Juliana (Journal of International Conference Proceedings, 2024)
The rapid advancement of internet technology has revolutionized everyday life, making online shopping a common phenomenon. Apart from that, with the development of technology, it can change several habits in human life, for example, shopping at the store can now be done via smartphone (online). Technological advances and the development of online shopping have certainly increased competition between businesses, encouraging them to adopt innovative digital promotional strategies. Live streaming features on e-commerce platforms have emerged as a popular tool for businesses to showcase their products and interact with potential buyers. This research aims to determine the influence of social presence on purchase intentions mediated by immersive experiences among Indonesian consumers who engage in live video commerce. The population in this study is Indonesian people who live in West Java with an age range of 14–29 years (1995–2010) and are classified as members of generation Z. It is hoped that these findings can provide valuable insights for businesses to optimize their live streaming campaigns and encourage sales.Keywords: Social Presence, Immersive Experience, Purchase Intention, E-Commerce, and Live Streaming.